Culture shock as a social issue - Sharipjonova Gulzoda Baxtiyorjon qizi (Periodica Journal, 2023)
This article is analyzed considering the social problem of culture shock. Also, in this article, what is culture shock? What are its consequences? We are talking about the nature of culture shock as a social problem
Keywords: culture shock; social issue; cultural exchange